The exposure assessment of airborne particulates matter (PM10 & PM2.5) towards building occupants: a case study at KL Sentral, Kuala Lumpur, Malaysia - Mohd. Din, Shamzani Affendy; Aminuddin, N M (IOP Publishing, 2014)
Airborne particulates have been recognized as a crucial pollutant of indoor air. These pollutants can contribute towards poor indoor air quality (IAQ), which may affect human health in immediate or long term. This study aims to determine the level of IAQ and the effects of particulate towards occupants of office buildings (the office buildings selected for the case study are SSM, KTMB and MRCB at KL Sentral). The objectives of study are (i) to measure the level of airborne particulates that contribute to the IAQ during working hours, (ii) to compare the level of airborne particulates with the existing guidelines and standards of IAQ in Malaysia and other Asian countries and (iii) to assess the symptoms associated with airborne particulates among the building occupants, which were achieved through primary data collection (case study or site survey, structured interview and questionnaire survey) and supported by literature reviews. The results showed that the mass concentration level of airborne particulates within the areas has exceeded the allowable limit of 0.15mg/m3 by IAQ Code of Practice, 2005 of the Department of Safety and Health (DOSH), Malaysia and 0.05mg/m3 by the Department of Environmental (DOE) (outdoor) of 8 hours continuous sampling. Based on the findings, the highest mass concentration values measured is 2.581 mg/ m3 at lobby of SSM building which is the highest recorded 17 times higher from the maximum limit recommended by DOSH than the others. This is due to the nearby construction works and the high numbers of particulates are generated from various types of vehicles for transportation surrounding KL Sentral. Therefore, the development of Malaysian Ambient Air Quality Guidelines on PM2.5 as one of the crucial parameters is highly recommended.